Calculation of combustion air required for burning solid fuels (coal / biomass / solid waste) and analysis of flue gas composition. (February 2020) - Paraschiv, Lizica Simona; Serban, Alexandru; Paraschiv, Spiru
Abstract: In power plants or any combustion systems, for a maximum efficiency of combustion, an operational safety procedure (reduction of CO emissions) and environmental pollution reduction, it is highly important to determine and monitor the flue gas composition resulting from burning of solid fuels in combustion chambers. The paper presents the development of a web application, which can prove extremely useful for thermo-energetic engineers and researchers who wish to perform combustion calculations of the solid fuels (coal / biomass / solid waste materials). The application allows users to enter the data on the elemental composition of the analyzed fuel, excess air and fuel flow rate to determine volume of oxygen and air necessary for fuel combustion and flue gas volume. This web application can be also successfully used both in designing stage of the combustion equipment and in the operating stage since the chemical composition of solid fuels is extremely variable (particularly in the case of waste materials) consequently it is highly important to know the optimum quantity of air required for a maximum efficiency of combustion. Proper control of the combustion process will lead both to the optimum functioning of the equipment and to less polluting combustion gasses and will also reduce thermal losses.